PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL NATIONAL GEOGRAPHIC INDONESIA CHANNEL TERHADAP MOTIVASI BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS VIII SMP NEGERI 1 PANTI - Nazar, Ayu; Suma, Nasobi Niki (TSAQIFA NUSANTARA: Jurnal Pembelajaran dan Isu-Isu Sosial, 2025)
This study aims to determine the effect of using the National Geographic Indonesia Channel audiovisual media on learning motivation in Social Studies subjects among Grade VIII students of SMP Negeri 1 Panti. This research is motivated by the lack of student motivation in learning Social Studies. The study employs a quantitative method with a pre-experimental type using a One Group Pretest-Posttest Design. The sampling technique used is purposive sampling, with a total sample of 32 students from class VIII F. Data collection techniques include observation, questionnaires, and documentation. The data analysis was conducted using the Paired Sample T-test, which showed that the calculated t-value (18.808) > t-table value (1.697), and the significance value (2-tailed) was 0.000 < 0.05. Therefore, it can be concluded that the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. Hence, it can be inferred that there is a significant effect of using the National Geographic Indonesia Channel audiovisual media on students' learning motivation in Social Studies at Grade VIII of SMP Negeri 1 Panti. Keyword: Audio Visual Learning Media, National Geographic Indonesia Channel, Student Learning Motivation, Social Studies Learning.